Stella, the Star Fairy - Meadows, Daisy (New York : Scholastic, 2008)
Rachel and Kirsty must help Stella, the Star Fairy, find the missing Christmas ornaments before Jack Frost and his goblins find them and make Christmas miserable for everyone.
Originally published: London : Orchard, 2005.
Accelerated Reader AR
Keywords: Fairies -- Juvenile fiction; Frost, Jack (Fictitious character) -- Juvenile fiction; Goblins -- Juvenile fiction; Lost articles -- Juvenile fiction; Christmas decorations -- Juvenile fiction